Risk of self-harm in patients with hypochondriasis: a population-based cohort study - Tang, Wai Kwong; Tsoi, Kelvin K. F.; Yip, Terry Cheuk Fung; Liew, Vivien Wei Jun; Chan, Selina Kit Yi (Frontiers in Psychiatry, 2025)
ObjectiveThis study aimed to ascertain whether individuals diagnosed with hypochondriasis (HYPO) exhibit a heightened risk of self-harming behaviors in comparison to those without the disorder.MethodsIn this matched cohort study, we conducted a review of electronic health records of all patients admitted to Hong Kong public hospitals for any reason between January 1, 1993, and December 31, 2022. A HYPO cohort comprising 906 patients was identified, along with a comparison cohort of 906 matched subjects. All participants were followed until the occurrence of a self-harm diagnosis, death from other causes, or the end of 2023, whichever came first. The risk of self-harm from the onset of HYPO was estimated using Cox proportional hazards regression models and competing risk analysis.ResultsOver the 30-year duration of the study, the number of individuals exhibiting self-harm behavior was 51 (5.6%) in the HYPO group and 49 (5.4%) in the comparison group. Both groups demonstrated comparable proportions of subjects engaging in self-harm (χ2 = 0.01, p = 0.927). The incidence rates of self-harm were 43.4 per 10,000 person-years in the HYPO group and 38.2 per 10,000 person-years in the comparison group. After adjustment, the hazard and subhazard ratio for self-harm in the HYPO group relative to the comparison group was 0.87 (95% confidence interval, 0.55–1.38) and 0.84 (95% CI, 0.53–1.34; p = 0.474), respectively.ConclusionsWe did not find significant evidence for an elevated risk of self-harm associated with HYPO. Future research is warranted to replicate these findings and to more comprehensively identify the potential unique risk factors for self-harm in this patient population.